2017
DOI: 10.2116/analsci.33.1305
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Extractabilities of Tetrachloro- and Tetrabromopalladate(II) Ions with a Thiodiglycolamide Compound

Abstract: Using N, N,N′, in n-dodecane as the extractant, we compared the percentages of Pd(II) extracted from HCl and HBr solutions, and analyzed the structures of the Pd(II)-extractant complexes. For comparison, similar experiments were performed with di-n-hexyl sulfide (DHS), a well-known sulfide-type extractant. TEHTDGA extracted Pd(II) from both HCl and HBr solutions much faster than DHS. The Pd(II)/(TEHTDGA or DHS) stoichiometry in the organic phase was 1:2. For TEHTDGA, the extractability of Pd(II) from HBr solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The mixture was stirred for 4 h before filtering any undissolved Pd(NO 3 ) 2 . The resulting solution was kept at room this behavior seems to be due to the involvement of the amide groups [22]. Hence, our results indicated that the coordination of the amide oxygen atoms would depend on the HNO 3 concentration in the aqueous phase.…”
Section: Solvent Extractionmentioning
confidence: 59%
“…The mixture was stirred for 4 h before filtering any undissolved Pd(NO 3 ) 2 . The resulting solution was kept at room this behavior seems to be due to the involvement of the amide groups [22]. Hence, our results indicated that the coordination of the amide oxygen atoms would depend on the HNO 3 concentration in the aqueous phase.…”
Section: Solvent Extractionmentioning
confidence: 59%
“…Specifically, powdered AMP03 containing 0.75 mmol/g Pd(II) was pelletized, and 0.5 and 7.0 M HNO 3 solutions containing 25 mM and 0.1 M Pd(II), respectively, were prepared. The EXAFS spectra of the pellet and the solutions were measured and analyzed as described elsewhere [15].…”
Section: Ft-ir and Exafs Measurementsmentioning
confidence: 99%